If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(-2x + 1) = 15(x + 1) Reorder the terms: 8(1 + -2x) = 15(x + 1) (1 * 8 + -2x * 8) = 15(x + 1) (8 + -16x) = 15(x + 1) Reorder the terms: 8 + -16x = 15(1 + x) 8 + -16x = (1 * 15 + x * 15) 8 + -16x = (15 + 15x) Solving 8 + -16x = 15 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 8 + -16x + -15x = 15 + 15x + -15x Combine like terms: -16x + -15x = -31x 8 + -31x = 15 + 15x + -15x Combine like terms: 15x + -15x = 0 8 + -31x = 15 + 0 8 + -31x = 15 Add '-8' to each side of the equation. 8 + -8 + -31x = 15 + -8 Combine like terms: 8 + -8 = 0 0 + -31x = 15 + -8 -31x = 15 + -8 Combine like terms: 15 + -8 = 7 -31x = 7 Divide each side by '-31'. x = -0.2258064516 Simplifying x = -0.2258064516
| 4x+16=24x-24 | | -3p+8=5-(8p+3) | | -6w+5=7-4w | | x(6x-1)=(6x+1)(x-5) | | -6w+5=7-w | | -4+13=17x-3-16x | | 8(4x-4)=4(8x+8) | | 218=27(x)+10 | | 5-c=24 | | -3z=45 | | 4x+16=21x-21 | | 3k-4=5k-6 | | -4(t+3)=12 | | 30-14=2(x-5) | | 6x-2=7x+2 | | 8+2y-6=5y+11-2y | | 6(5x-1)+4(13-5x)-3(3x+1)=-1 | | 2(z+5)+4=12 | | b=hq | | 3a-6a+4(a-4)=-2(a+2) | | 14x+11=14x-11x | | 9+4s-2=8s+15-2s | | -5(6x-10)=230 | | 3(5+x)= | | 4(9c-1)-2=34c+4 | | -3y-11=6y+52 | | 7x-5-2x=x+8+x | | 2f-4=2f+4 | | -9c+1=-44 | | 2t-3=3(t+7) | | 4(y-3)=y-12 | | -14x-20=-13x+50 |